Transport evidence of asymmetric spin–orbit coupling in few-layer superconducting 1Td-MoTe2 - Cui, Jian (2019)
Two-dimensional transition metal dichalcogenides MX2 (M = W, Mo, Nb, and X = Te, Se, S) with strong spin–orbit coupling possess plenty of novel physics including superconductivity. Due to the Ising spin–orbit coupling, monolayer NbSe2 and gated MoS2 of 2H structure can realize the Ising superconductivity, which manifests itself with in-plane upper critical field far exceeding Pauli paramagnetic limit. Surprisingly, we find that a few-layer 1Td structure MoTe2 also exhibits an in-plane upper critical field which goes beyond the Pauli paramagnetic limit. Importantly, the in-plane upper critical field shows an emergent two-fold symmetry which is different from the isotropic in-plane upper critical field in 2H transition metal dichalcogenides. We show that this is a result of an asymmetric spin–orbit coupling in 1Td transition metal dichalcogenides. Our work provides transport evidence of a new type of asymmetric spin–orbit coupling in transition metal dichalcogenides which may give rise to novel superconducting and spin transport properties.